SOSIALISASI PERAN ORANG TUA TERHADAP MOTIVASI BELAJAR ANAK DIERA NEW NORMAL PADA TIM PENGGERAK PKK DESA SIDORAHAYU (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
The family as the first education center is the parents who are the first educators for their children because from the parents the child receives the first education, thus the first education. The aim is to find out how the role of parents in motivating their children to learn. The methods of parents in motivating children are: giving gifts, punishment by reducing pocket money and limiting playing habits. Parents are fathers and mothers who have an important and very influential role in the education of their children. The role of parents in children's education should be the main thing, it is the parents who understand the good and bad qualities of their children. What do they like and what they don't like. As well as supervising children's learning when children study at home and supervising children's learning difficulties and finding solutions for children with learning difficulties. The conclusion is that parents have a very important role in the education of their children, including as a motivator. Parents must always give encouragement to their children so that they are enthusiastic in learning and the role of parents in motivating children as motivators to support children.